NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIATotal orthotopic heart transplantation in 6-month old child - Hrapkowicz, Tomasz; Zakliczyński, Michał; Chodór, Beata; Śliwka, Joanna; Kubacki, Krzysztof; Przybylski, Roman; Pasek, Piotr; Grzybowski, Adam; Borkowski, Jarosław; Białkowski, Jacek; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Heart transplantation is the best therapeutic option for end-stage heart failure for both adults and pediatric patients. The short- and long-term outcomes of pediatric heart transplantation are improving significantly, although the lack of donors impede wide clinical application. In this paper we describe a successful heart transplantation in the youngest in Poland at the moment of surgery a 6-month old recipient.